Start-Up and Fraud Shenanigans: Case Study on Start-Ups Affiliated with Public Companies - Ruri Octari Dinata; Annisa Nurbaiti (Asia Pacific Fraud Journal, 2022)
This study explains how fraud occurs in start-up companies. This study uses qualitative method with thick description technique with the aim of investigating current events and directing them to concepts and theories by utilizing information obtained from informants. The results of this study show that shenanigans were initially formed from a culture shock that led to a fraud in the form of corruption that harmed many parties, including investors. This happens because fraud has become a culture and the company leaders have lost their integrity. The novelty of this research lies in the type of fraud committed by fraud perpetrators that occur in start-up companies.